Management of Equality Education Program in Daarut Tauhiid Community Learning Center (CLC) - Hasanah, Viena Rusmiati; Ardiwinata, Jajat Sudrajat; Hatimah, Ihat; Wulandari, Hodijah (Universitas Negeri Semarang, 2021)
Education services for certain groups who have learning needs for 12 years of compulsory education other than through formal education can be served through non-formal and informal channels, which are called equality education. This study aims to describe the equality education management program at the Daarut Tauhiid Community Learning Center (CLC) as seen from the management function, namely planning, implementation and evaluation. The research was conducted through a qualitative approach with a participatory exploratory method, using participatory observation techniques, in-depth interviews, and FGDs. The results showed that the equality education program at Daarut Tauhiid CLC consisted of planning that included the needs of the students, determining goals, recruiting teachers and students, preparing learning tools and providing facilities and infrastructure. Meanwhile, the implementation of the program is carried out with a learning pattern in the form of face-to-face, tutorial and independent learning based on the 2013 curriculum. For evaluation, PKBM DT conducts program evaluations internally and externally and evaluates the students.